Rhodamine B Adsorption- Kinetic, Mechanistic and Thermodynamic Studies - S. Ramuthai; V. Nandhakumar; M. Thiruchelvi; S. Arivoli; V. Vijayakumaran (E-Journal of Chemistry)
Adsorption of rhodamine B from aqueous solution on the surface of Moringa oliefera bark carbon was accomplished under the optimize conditions of temperature, concentration, pH, contact time and quantity of adsorbent. Spectrometric technique was used for the measurements of concentration of dye before and after adsorption. The percentage removal of rhodamine B was calculated. The values of % adsorption data for Moringa oliefera bark carbon system show better adsorption capacity. The experimental data are fitted to the Langmuir and Freundlich isotherm equations. The values of their corresponding constant were determined from the slope and intercepts of their respective plots. Thermodynamic parameters like ΔG0, ΔH0 and ΔS0 were calculated. Rhodamine B-Moringa oliefera bark carbon system shows spontaneous and endothermic behaviour. The results of these investigations suggested that natural adsorbents can be utilized as adsorbent materials, because of their selectivity's for the removal of dyes.